Modelling the curing kinetics of DGEBA-MTHPA with DMP-accelerator concentration dependence - H. Möllers; C. Schmidt; D. Meiners (Polymer Testing)
The curing of epoxy anhydride systems is often modelled using various phenomenological models. These models give a relationship between the cure rate and the temperature and degree of cure of the resin. Typically, epoxy anhydride systems are used in combination with an accelerator to lower the cure temperature and speed up the cure process. In this study, the influence of 2,4,6-Tris(dimethylaminomethyl)phenol (DMP) accelerator on the cure kinetics of a Bisphenol A diglycidyl ether (DGEBA or BADGE)-Methyltetrahydrophthalic anhydride (MTHPA) mixture was investigated using isothermal and dynamic modulated differential scanning calorimetry (MDSC) measurements. As expected, the accelerator increased the cure rate and lowered the reaction start temperature. The Kamal-Sourour model, incorporating a Fournier diffusion factor, was successfully fitted to the MDSC data. The Kamal-Sourour parameters indicate that the accelerator primarily affects the non-autocatalytic part of the reaction. Increasing the accelerator concentration also resulted in earlier vitrification of the resin up to 6 % degree of cure and 3–4% higher achievable cure degrees at isothermal temperatures. The effect of the accelerator was integrated into the Kamal-Sourour model, yielding a set of parameters that can be used to calculate the cure rate as a function of temperature, cure degree, and accelerator concentration with a mean error of 3.5 %.